(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Antibodies formed in response to the introduction of antigens into the body interact specifically with these antigens. The primary interaction is based on the general principles of any bimolecular reaction. Since in this case the product of the reaction is an antigen-antibody complex, the immune reaction is reversible and is described by the same kinetic and thermodynamic parameters as any complexation process.